Implementation of an Institutional Mathematics Curriculum: From Expectation to Reality - Poveda-Vásquez, Ricardo; Zumbado-Castro, Marianela (Revista Electrónica Educare, 2023)
Objective. This research aimed to analyze the implementation of the mathematics curriculum of a private primary school located in an urban area of Costa Rica. Methodology. It was developed under the post-positivist paradigm, with a mixed design that used content analysis and descriptive statistics. Analysis of results. The review of teachers’ didactic plans, student notebooks, and applied written tests allowed a comparison with the institutional mathematics curriculum and generated inputs for decision-making. Conclusions. It is determined that, during the implementation, the teachers dedicate much time to the area of numbers, neglecting the other mathematical areas. This is evidenced in the number of items included in the written tests. Recommendations. The main recommendation is associated with adjusting the plans for the third school period of that year to correct the problem found; participant observation is also proposed as a complementary tool for future assessment.